Trends and resource recovery in biological wastewater treatment system. (September 2019) - Meena, Ramakrishnan Anu Alias; Yukesh Kannah, R; Sindhu, J; Ragavi, J; Kumar, Gopalakrishnan; Gunasekaran, M; Rajesh Banu, J
Abstract: Nutrient removal from wastewater is an essential task to protect natural water resource and its excess results in eutrophication. Faster resource depletion and environmental sustainability paves the way for wastewater treatment and resource recovery and bioelectrochemical systems (BES) were employed to attain the goal. The first generation, BES, microbial fuel cell (MFC), microbial electrochemical cell (MEC) and microbial desalination cells (MDC) were getting really good with wastewaters. However, to achieve improved performance, BESs with membrane systems (OsMFC and FO-OMBR) and combination systems (MFC-MEC; MEDCC) were introduced. This review pointed out that high strength wastewaters can enhance nutrient recovery and electricity generation. This review aims to explore the recovered sources in various states of matter as solid, liquid, gas and energy. Moreover, limiting factors for resource recovery such as membrane fouling, reverse solute flux, internal resistance, substrate type and COD removal efficiency are highlighted. Finally, future research prospects have been discussed. Highlights: Increasing nutrient content threatens wastewater treatment systems. High power density was not achieved in BES with municipal wastewater till date. Osmotic and hybrid BES enhance phosphorus and hydrogen recovery than standalone BES. High strength wastewaters enhance nitrogen recovery and electricity production. Internal resistance, reverse solute flux and fouling are still challenging factors.